Matienzo’s reflection on the theory of value and the organicist discursive topic - Doardi, Davide (2025)
The training of social science researchers requires an epistemological positioning, which implies activating philosophical knowledge that, on occasions, was not adequately addressed during undergraduate training. This requirement can cause the study of epistemology to be perceived as excessively abstract or lacking in practical relevance. In view of this perception, a methodological analysis was undertaken based on personal experience, delimiting both the normative dimension of the subject and its pedagogical justifications. Subsequently, in order to strengthen its historical understanding, the origin of epistemological thought in classical antiquity was reconstructed. The results show a close relationship between epistemological reflection and the development of transversal competencies. They also show how ancient epistemology tends towards a universalizing and deductive paradigm, the validity of which enters into crisis with the emergence of the social sciences in modernity. It is concluded that the study of ancient epistemology in graduate education is not only justified by its value in the construction of a critical self- understanding of the role of the researcher in the field of social sciences, but also by its contribution to the development of soft skills.